Secreted frizzled-related protein 5 promotes angiogenesis of human umbilical vein endothelial cells and alleviates myocardial injury in diabetic mice with myocardial infarction by inhibiting Wnt5a/JNK signaling. Issue 5 (2nd May 2022) - Ding, Nian; Zheng, Chenghong
ABSTRACT: The purpose of this study is to investigate whether secreted frizzled-related protein 5 (SFRP5) affects the proliferation, migration and angiogenesis of human umbilical vein endothelial cells (HUVECs) induced by high glucose (HG). HUVECs were treated with different concentrations of glucose. MTT, wound healing, angiogenesis, and ELISA assays were used to detect cell cytotoxicity, migration, tube formation, and VEGF165 and VEGF165b levels, respectively. The mice model of type 2 diabetes mellitus (T2DM) complicated with myocardial infarction (MI) was established. SFRP5 was injected intrabitoneally for 2 weeks. cardiac output (CO), left ventricular ejection fraction (LVEF) and left ventricular shortening fraction (LVSF) were detected by echocardiography. Western blot was used to detect the protein levels of SFRP5, Wnt5a, JNK1/2/3, p-JNK1/2/3, TGF-β1, Caspase3, Bax, and Bcl-2. The expression of SFRP5 was declined in HG-induced HUVECs and T2DM-MI. Intervention of SFRP5 promoted the migration of HUVECs and angiogenesis, as evidenced by a lower expression of Bax and caspase3, but a higher expression of Bcl-2. Meanwhile, SFRP5 inhibition repress Wnt5a and p-JNK expression. Howerver, The JNK inhibitor (SP600125) enhanced the down-regulation of Wnt5a/JNK pathway proteins by SFRP5. SFRP5 intervention increased the levels of CO, LVSF, and LVEF in T2DM-MI mice. SFRP5 inhibited myocardial pathological injury and fibrosis in T2DM-MI mice and SFRP5 could down-regulate Wnt5a and p-JNK1/2/3 activation. SFRP5 promotes the proliferation, migration and angiogenesis of HUVECs induced by HG, and inhibits cardiac dysfunction, pathological damage, fibrosis, and myocardial angiogenesis in diabetic myocardial ischemia mice, which is achieved by inhibiting Wnt5a/JNK signaling.